ANALISIS BANTUAN LANGSUNG TUNAI TERHADAP PENDAPATAN MASYARAKAT DI DESA SEPAKAT KECAMATAN PLAMPANG (STUDI KASUS DI DESA SEPAKAT KECAMATAN PLAMPANG) - Nurfadliyah, Nurfadliyah; Putri, Novida Halleine (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
This study aims to determine Direct Cash Assistance to Community Income. The variables of this study are Direct Cash Assistance and Community Income. The analysis technique used is simple linear regression analysis and hypothesis testing t test. The Adjusted R value is 0.099 or 9.90%, which means a very weak correlation between cash transfers and people's income. For an Adjusted R value of 0.010 or 1.00%, the distribution of direct cash assistance is influenced by people's income, while 99.00% is influenced by other variables. The results of the t-test test between direct cash assistance to community income obtained a significance value of 0.276 or 27.6% is greater than 0.05 or 5%. So it can be concluded that direct cash assistance has no effect on people's income in Sepakat Village, Plampang District, Sumbawa Regency.